Processing representation and learnability of the resultative construction by brazilian portuguese-english bilinguals - Candido Samuel Fonseca de Oliveira (2016)
This Ph.D. dissertation addresses possible bilingualism effects on speakerslinguistic processing and representation through a psycholinguistic methodology. Ourprimary focus is the analysis of how bilingualism can influence bilinguals first language(L1), but we also investigate possible phenomena present in the acquisition of a secondlanguage (L2)-specific structure. More specifically, the research objectives are (i) toverify whether bilinguals exhibit reduced processing cost to read an L2-specificconstruction in the L1, (ii) to analyze whether these bilinguals accept this construction intheir L1 and (iii) to investigate if bilinguals learn both the licensed and the unlicensedfeatures of this construction in the L2. The participants are highly proficient BrazilianPortuguese (BP)-English bilinguals immersed either in the L1 or in the L2. The targetstructure is the resultative construction (e.g., Samuel wiped the table clean) and ourcontrol structure is the depictive construction (e.g., Samuel ate the salmon raw). Bothconstructions are grammatical in English, but only the depictive is licensed in BP.Furthermore, we observe how the participants process and perceive some ungrammaticalresultative sentences (e.g., Samuel twisted the toy broken) in English. In order to reachthe research objectives, we conducted a series of experiments using the Maze Task (MT)and the Acceptability Judgment Task (AJT) paradigms in both BP and English. Theresults from the experiments in BP indicate that both immersed and non-immersedbilinguals process the adjective in the resultative construction significantly faster than BPmonolinguals. However, bilinguals and monolinguals perceived the resultativeconstruction as less acceptable than the depictive construction. These results suggest thatbilingualism can exert influence on L1 linguistic processing, but such influence does notresult in changes in bilinguals overall L1 grammar, at least in regards to the constructions under scrutiny. The data from the experiments in English indicates that bilinguals andmonolinguals process the resultative construction as fast as they process the depictiveconstruction. They also show an additional processing cost when reading theungrammatical resultative sentences. Moreover, bilinguals and monolinguals do notdiffer significantly from each other in their acceptability judgments of the resultativesentences in English, but bilinguals give significantly higher acceptability ratings to theungrammatical resultative sentences as compared to monolinguals. These results suggestthat bilinguals can learn L2-specific constructions, but they are less sensitive to L2-specific restrictions than monolinguals are. We discuss all these findings in light ofdifferent theoretical perspectives, among which we highlight the Multi-Competence, theMultiple-Grammars and the Negative Evidence hypotheses.